2015
DOI: 10.1128/iai.02832-14
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of Pro- and Anti-Inflammatory Properties of Staphylococcus aureus

Abstract: Staphylococcus aureus is a Gram-positive bacterium that is carried by a quarter of the healthy human population and that can cause severe infections. This pathobiosis has been linked to a balance between Toll-like receptor 2 (TLR2)-dependent pro-and anti-inflammatory responses. The relationship between these two types of responses is unknown. Analysis of 16 nasal isolates of S. aureus showed heterogeneity in their capacity to induce pro-and anti-inflammatory responses, suggesting that these two responses are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…S. aureus-induced IL-10 production by monocytes/macrophages is critically TLR2 dependent and, importantly, it appears that S. aureus-induced pro-and antiinflammatory cytokine production by these cells can be uncoupled due to the organism's capacity to manipulate TLR2 plasticity and engage unique downstream signaling pathways (33). We now demonstrate that IL-10 production by B1a cells is also TLR2 dependent.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…S. aureus-induced IL-10 production by monocytes/macrophages is critically TLR2 dependent and, importantly, it appears that S. aureus-induced pro-and antiinflammatory cytokine production by these cells can be uncoupled due to the organism's capacity to manipulate TLR2 plasticity and engage unique downstream signaling pathways (33). We now demonstrate that IL-10 production by B1a cells is also TLR2 dependent.…”
Section: Discussionmentioning
confidence: 57%
“…8A). Previous studies have indicated that S. aureus-induced IL-10 production by macrophages is TLR2 dependent (33). To investigate a potential role for TLR2 in B1a cell activation by S. aureus, we cultured naive B1a cells isolated from WT or TLR2 2/2 mice in the presence of live S. aureus (MOI of 100).…”
Section: Il-10 Protects Against Host Morbidity and Mortality During Amentioning
confidence: 99%
“…More precisely (16), MDR E. coli induced a potent early production of proinflammatory cytokines, followed by low release of IL-10; this was accompanied by prolonged survival in an experimental sepsis model in rabbits much resembling the findings of K. pneumoniae. Peres et al (17) showed that Staphylococcus aureus isolates have differential capacities to induce pro-and anti-inflammatory cytokine production by human monocytes, implicating that these responses may determine colonization and disease tolerance versus pathogenicity and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus (S. aureus) induces the production of IL-10 by monocytes, macrophages and B1a cells in a TLR2-dependent manner [125,126]. IL-10 contributes in pathologic events during acute localized S. aureus infection by inhibiting local proinflammatory cytokine production.…”
Section: Accepted Manuscriptmentioning
confidence: 99%